Integration Discourse: Modern and Postmodern - Dueck, Alvin C. (Journal of psychology and theology, 2004)
Psychologists and theologians are culture bound beings whose construals take place within history such that traces of the social context flow into their scholarly dialogue. The authors argue for the legitimacy of diverse voices –- modern and postmodern –- as they emerge in a sample of theologies and psychologies. It is proposed that conscious and unconscious precommitments to modern and postmodern assumptions shape the dialogue between psychologists and theologians. Three criteria will be used to differentiate discourses: epistemological foundationalism, autonomous individuality and the universality of scientific knowledge. While each discourse may limit the way spirituality is expressed, the authors argue that the differences in discourse should be recognized and explored.